Comparison of Arbekacin and Vancomycin in Treatment of Chronic Suppurative Otitis Media by Methicillin Resistant Staphylococcus aureus - Hwang, Ji-Hee (The Korean Academy of Medical Sciences, 2015)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of ear infections. We attempted to evaluate the clinical usefulness of arbekacin in treating chronic suppurative otitis media (CSOM) by comparing its clinical efficacy and toxicity with those of vancomycin. Efficacy was classified according to bacterial elimination or bacteriologic failure and improved or failed clinical efficacy response. Ninety-five subjects were diagnosed with CSOM caused by MRSA. Twenty of these subjects were treated with arbekacin, and 36 with vancomycin. The bacteriological efficacy (bacterial elimination, arbekacin vs. vancomycin: 85.0% vs. 97.2%) and improved clinical efficacy (arbekacin vs. vancomycin; 90.0% vs. 97.2%) were not different between the two groups. However, the rate of complications was higher in the vancomycin group (33.3%) than in the arbekacin group (5.0%) (P=0.020). In addition, a total of 12 adverse reactions were observed in the vancomycin group; two for hepatotoxicity, one for nephrotoxicity, eight for leukopenia, two for skin rash, and one for drug fever. It is suggested that arbekacin be a good alternative drug to vancomycin in treatment of CSOM caused by MRSA.